Pendekatan Discrete Event Simulation untuk Peningkatan Sistem Produksi Pada Perishable product - Jamil, Nofal; Pulungan, Muhammad Almaududi; Yastica, Tiara Verita (Universitas Al Azhar Indonesia, 2025)
Bottlenecks in perishable products processing have significantly decrease the number of sweet potato paste production at PT. XYZ, which have lead to the decrease of more than 23.44% in the fulfillment of the number of demand and result in 2023. These problems are also caused by suboptimal production planning, lack of efficiency in the production process, the occurrence of raw material bottlenecks in the production process, suboptimal resource management and the occurrence of many rejections in the finished good. This study aims to overcome bottlenecks that occur in order to increase the amount of sweet potato paste production. The methodology of this study uses the discrete event simulation approach. This study applies a confidence level of 95% in the existing simulation model. Of the 20 scenario models that have been built, the best four models were further evaluated based on the output and cost aspects. The best of the four is scenario model 13 with the addition of 1 shift in the entire production process, namely the sorting process to the outer packing process with the addition of 105 workers. This scenario produced 1,274,527 kg of products for 10 months and a percentage increase in the amount of output of 72.74%, gross profit value of IDR 4,016,084,955.50 and marginal profit value of IDR 778.82 with additional direct labor costs of IDR 2,199,145,960 for 10 months and investment costs of IDR 0.Keywords – Bottleneck, Discrete Event Simulation, Gross Profit, Marginal Profit, Perishable product.